Szybkość, skala i koszty realizaji programu antykrysowej pomocy rządowej dla sektora bankowego Irlandii w latach 2008–2009 - Pękala, K.; Ziąber, P. (Видавництво Національного університету "Львівська політехніка", 2009)
The thesis breaks down the correlation between certain events in relation to the current crisis in the Republic of Ireland and the reaction taken by the Irish Government. Moreover, extra recovery costs were shown to avoid further disturbances on the international financial markets. After Lehman Brothers' failure Ireland responded rapidly by taking determined action to prevent the lack of liquidity in the Irish banking sector. This reaction was approved by the European Commission which helped other European Governments to provide national guarantees for their home financial institutions.